Morpho-functional characterization of an elite Chilean mountain runner: insights from a high-performance case study - Nieto-Jiménez, C; Baez-San Martin, E; Rojas-Valverde, D; Yáñez-Sepúlveda, R; Tuesta, M. (Journal of Human Sport & Exercise, 2025)
Trail running (TR) is an endurance sport practised on irregular natural terrain with significant elevation changes. The aim was to analyse cardiorespiratory fitness parameters, bilateral body composition and maximal strength profiles in the lower limbs of elite Chilean trail runners. A 26-year-old Chilean amateur ultra trail runner was studied (body weight: 62.3 kg, height: 1.71 m, BMI: 21.2 kg/m², lean mass: 54 kg (86.6%), muscle mass: 30.3 kg (48.6%), fat mass: 8.3 kg (13.3%) and a skeletal muscle mass index of 7.5 kg/m²). The subject participated in three laboratory sessions: 1) anthropometric and pulmonary measurements, 2) cardiopulmonary exercise testing (CPET) with heart rate variability (HRV) assessment, and 3) isometric and isokinetic lower limb strength assessment. During the CPET, VO2max, ventilatory and HRV thresholds were measured using the DFA a1 algorithm. Quadriceps muscle oxygen saturation (SmO2) was also recorded. The runner presented a VO2max of 75 ml/kg/min. SmO2 values during CPET were 67.2% at rest, 38.5% at VT1, 26.8% at VT2 and 17.2% at VO2max. The results showed that the first heart rate variability threshold (HRVT1) coincided with the ventilatory thresholds (VT1 and VT2). Isometric and isokinetic evaluation revealed a higher eccentric flexion/concentric extension ratio in the right hip compared to the left, with values of 2.58 for the right and 2.25 for the left. Aerobic fitness is essential for trail running performance. Ventilatory thresholds and HRV, together with SmO2, may be useful tools for monitoring muscle fatigue. The observed muscle strength imbalances between limbs highlight the importance of training for strength symmetry to maximise performance and reduce the risk of injury. Future studies on muscle oxygenation, respiratory function and muscle asymmetries may improve training strategies in TR.